Access to Medicines and Vaccines Implementing Flexibilities Under Intellectual Property Law - Correa, Carlos M.; Hilty, Reto M.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This open access book is the outcome of a Global Forum on Innovation, Intellectual Property and Access to Medicines held in December 2019 at the Max Plank Instititute in Munich, organised by the South Centre and the Max Plank Institute. The academics and experts from international organisations participating have contributed chapters to this book. The book is for policy makers (in Ministries of Health, Ministries of Trade, Ministries of Foreign Affairs, patent offices), but also relevant for academics (law, trade, public health), on the flexibilities available in the Agreement on Trade Related Aspects of Intellectual Property Rights (TRIPS) of the World Trade Organization to promote access to medicines.
Interpreting the flexibilities under the TRIPS agreement -- Intellectual Property Exhaustion and Parallel Imports of Pharmaceuticals: A Comparative and Critical Review -- Compulsory license and government use -- Access to genome editing technologies -- Bolar exception -- Patent oppositions in India -- Protection of clinical test data -- Courts and Pharmaceutical Patents -- Robust Patent Examination or Deep Harmonization? Cooperation and Work Sharing between Patent Offices -- IPRs, Competition Law and excessive pricing of medicines -- The impact of TRIPS plus rules -- Patent Linkages and its Impact on Access to Medicines.
Keywords: Information technology$1 (BLaw and legislation.s; Mass media$1 (BLaw and legislation.s; Medicine$1 (BResearch.s; Biology$1 (BResearch.s; International law; Trade regulation; Medical economics; IT Law, Media Law, Intellectual Property; Biomedical Research; International Economic Law, Trade Law; Health Economics